'Maravalgate' and its effects: a year of debate over the funding of French cinema. Issue 2 (3rd May 2016) - Nacache, Jacqueline
Abstract: The French system of film funding allows French cinema to resist the hegemony of Hollywood better than any other European cinema. It is a reflection of France's protective stance regarding its cultural products, a position that has long been expressed in its strong defence of the principle of 'cultural exception' in free trade agreements between the European Union and the United States. It might be thought that an arrangement that is so favourable to film production would receive unanimous support. On the contrary, it fuels controversy and is regularly criticised and even attacked. An example of this is producer Vincent Maraval's claim at the end of 2012 that French actors are 'overpaid'. This opinion piece had considerable repercussions because it called the funding system of French cinema into question. Its effects are still being felt today. This article will follow the thread of the discussion throughout 2013, a year that is a perfect case study because it presents an exceptional sequence of incidents and reactions around the question of film funding. Through their denunciation of the excesses linked to government assistance, criticism of the avance sur recettes (advance against earnings), rejection of the collective agreement, the fantasy of a cinema of 'public servants', and finger-pointing at films with low audiences, these reactions blurred the lines between supporters and opponents of the system. The author analyses the tensions and misunderstandings expressed in these debates, highlighting their often contradictory nature. She points out that these tensions have their origins in debates that significantly predate the very existence of cinema, because they follow in the footsteps of a traditional conflict in France between art and money. She above all stresses the fact that they have inherited a very old suspicion of any art form considered to be dependent on government support.